The Impact of Quran Memorisation on Wellbeing: Lived Experiences of Bohra Huffaz - Batul Lehri (International Journal of Trends in Humanities, 2025)
The Quran, revealed over 1400 years ago, remains central to Muslims' daily lives, particularly through recitation during prayers. Quran memorisation (QM), known as Hifz, is a centuries-old tradition requiring intense cognitive engagement, discipline, and spiritual dedication. While many studies explore the psychological benefits of spiritual practices, few have examined the profound impact of full Quran memorisation on personal well-being. This study examines how Quran memorisation influences psychological well-being, particularly among Indian individuals who have fully memorized the text (Huffaz). Using a qualitative phenomenological approach, this study conducted in-depth interviews with Huffaz from the Bohra community to explore their motivations, challenges, and psychological adaptations throughout their journey. The findings reveal that Quran memorisation fosters cognitive enhancements (including improved memory retention and attentional focus), emotional resilience, reinforcement of spiritual identity, a sense of security, and the development of discipline and self-regulation. Furthermore, participants experienced social and interpersonal transformations, such as changes in personal relationships, social roles, and self-perception. The study also found that the rigorous mental training involved in Hifz acted as an aid for future academic pursuits, with many Huffaz reporting greater ease in coping with academic demands due to their enhanced memorisation skills, concentration, and structured study habits. This research bridges the gap between spirituality and psychology. Mental health professionals working with religious individuals may benefit from incorporating faith-based coping strategies into therapeutic approaches. Understanding the psychological impact of such spiritual practices can contribute to holistic well-being frameworks in both educational and clinical settings.
Keywords: Quran memorisation (QM); cognitive enhancement; emotional resilience; spirituality; well-being